Penerapan Strategi Pemasaran Untuk Menigkatkan Penjualan Usaha Toko Bedcoverkuplg di Palembang Berdasarkan Perspektif Ekonomi Syariah - Ayu Nurhaliza; Hilda; Safitri Asrol (Lentera Jurnal Manajemen, 2026)
Competition in the digital business world requires Micro, Small, and Medium Enterprises (MSMEs) to implement effective marketing strategies that align with sharia principles. The purpose of this study is to analyze how marketing strategies are implemented to increase sales at the Bedcoverkuplg Store located in Palembang, and to evaluate the role of these strategies from a sharia economic perspective. The method used in this study is a descriptive qualitative approach with a field study approach, which includes observation, interviews, and document collection from the business owner, employees, and customers. The results show that the Bedcoverkuplg Store has implemented the 7P marketing mix, which is reflected in product quality, competitive prices, strategic location, promotions through social media platforms, good service, orderly operational processes, and a neat store appearance. From a sharia economic perspective, this business integrates the values ​​of honesty, transparency, fair prices, and guarantees of halal and thayyib products. This sharia-based marketing strategy has been proven to contribute to increased sales and strengthened customer trust and loyalty, although its growth has not been completely stable due to limited product variety and the use of digital marketing that still needs to be improved.